Biodistribution and elimination kinetics of systemic Stx2 by the Stx2A and Stx2B subunit-specific human monoclonal antibodies in mice. - Sheoran, Abhineet.; Jeong, Kwang-il.; Mukherjee, Jean.; Wiffin, Anthony.; Singh, Pradeep.; Tzipori, Saul. (2016)
Background: Hemolytic uremic syndrome (HUS) leading to acute kidney failure, is a condition linked to the production of primarily Shiga toxin 2 (Stx2) by some E. coli serotypes. We have previously shown that Stx2 A subunit-specific human monoclonal antibody (HuMAb) 5C12, and B subunit-specific HuMAb 5H8 inhibit cultured cell death, and protect mice and piglets from fatal Stx2-intoxication. We have also shown that 5H8 blocks binding of Stx2 to its cell-surface receptor globotriaosyl ceramide (Gb3), whereas Stx2 when complexed with 5C12 binds Gb3 with higher affinity than Stx2. The mechanism by which 5C12 neutralizes Stx2 in vitro involves trapping of Stx2 in the recycling endosomes and releasing it into the extracellular environment. Because of the clinical implications associated with the formation of Stx2/antibody complexes and the potential for trapping and clearance through a severely damaged kidney associated with HUS, we investigated the likely site(s) of Stx2/antibody localization and clearance in intoxicated mice treated with antibody or placebo.; Keywords: Shiga toxin, Radiolabel, Antibody, Toxin elimination, Toxin concentration, Pharmacokinetic, Human monoclonal antibody.; Springer Open.